2017
DOI: 10.3390/molecules22122142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Nitrogen-Containing Heterocycle Bromophenols and Their Interaction with Keap1 Protein by Molecular Docking

Abstract: We previously reported 5,2’-dibromo-2,4’,5’-trihydroxydiphenylmethanoe (LM49), a bromophenol analogue that shows strong protection from oxidative stress injury owing to its superior anti-inflammatory, antioxidant, and anti-apoptotic properties. A series of novel nitrogen-containing heterocycle bromophenols were herein synthesized by introducing substituted piperidine, piperazine, and imidazole to modify 2-position of the lead compound LM49. By further evaluating their cytoprotective activity against H2O2 induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Nrf2-Keap1 protein-protein interaction (PPI) has been recognized as a key point for regulating Nrf2 activation [37]. Keap1 depends on the interaction with the key tyrosines, namely Tyr525, Tyr574, Arg-415 and Tyr334 [38,39]. We confirmed that Arg415, Tyr334, Tyr525 were key amino acids for the interaction of carnosol with Keap1.…”
Section: Discussionsupporting
confidence: 58%
“…Nrf2-Keap1 protein-protein interaction (PPI) has been recognized as a key point for regulating Nrf2 activation [37]. Keap1 depends on the interaction with the key tyrosines, namely Tyr525, Tyr574, Arg-415 and Tyr334 [38,39]. We confirmed that Arg415, Tyr334, Tyr525 were key amino acids for the interaction of carnosol with Keap1.…”
Section: Discussionsupporting
confidence: 58%
“…When a series of nitrogen-containing heterocycles such as piperidine, piperazine, and imidazole replaced the OH group at the 2-position of 3.22 , the products also showed moderate to potent cytoprotective activity against H 2 O 2 -induced injury in EAhy926 cells with 3.24 ( Scheme 3 ; EC 50 = 0.9 μM) being the most potent compound. A SAR study revealed that the antiradical ability of these analogues strengthened with an increasing number of heterocycles and hydroxyl groups [ 42 ]. Furthermore, a molecular docking study demonstrated that compound 3.24 could interact with Keap1, and thus in turn modulate Keap1-Nrf2 protein–protein interaction in order to activate Nrf2-induced downstream protective genes from oxidative stress damage [ 42 ] (see Section 3 ).…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
“…A SAR study revealed that the antiradical ability of these analogues strengthened with an increasing number of heterocycles and hydroxyl groups [ 42 ]. Furthermore, a molecular docking study demonstrated that compound 3.24 could interact with Keap1, and thus in turn modulate Keap1-Nrf2 protein–protein interaction in order to activate Nrf2-induced downstream protective genes from oxidative stress damage [ 42 ] (see Section 3 ). Some novel synthetic diarylmethanone BPs 3.25–3.31 ( Scheme 3 ) also showed antiradical abilities.…”
Section: Bioactivities Of Bps and Potential Use In Medicinementioning
confidence: 99%
See 2 more Smart Citations